2017
DOI: 10.1164/rccm.201603-0596oc
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Primes Neutrophils for Neutrophil Extracellular Trap Formation during Sepsis

Abstract: These results indicate that neutrophil autophagy primes neutrophils for increased NET formation, which is important for proper neutrophil effector functions during sepsis. Our study provides important insights into the role of autophagy in neutrophils during sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 52 publications
3
101
0
1
Order By: Relevance
“…The observation that corticosteroids lead to a prolonged lower level of NETs in recovering patients who have a better outcome does perhaps suggest a beneficial role for NETosis during the process of recovering from pneumonia, and would be in keeping with other recent data suggesting that patients who survive sepsis may indeed have a greater ability to make NETs than non-survivors [24]. Recent data from CF patients has suggested that a delay in neutrophil apoptosis in these subjects leads to an increased ability to form NETs [21], suggesting that the activation of alternative routes of disposal for neutrophils may have consequences in terms of promoting inflammation.…”
supporting
confidence: 84%
“…The observation that corticosteroids lead to a prolonged lower level of NETs in recovering patients who have a better outcome does perhaps suggest a beneficial role for NETosis during the process of recovering from pneumonia, and would be in keeping with other recent data suggesting that patients who survive sepsis may indeed have a greater ability to make NETs than non-survivors [24]. Recent data from CF patients has suggested that a delay in neutrophil apoptosis in these subjects leads to an increased ability to form NETs [21], suggesting that the activation of alternative routes of disposal for neutrophils may have consequences in terms of promoting inflammation.…”
supporting
confidence: 84%
“…Because the phagocytic cells are encountered with pathogens, dysregulated immune response (Bangsgaard, Hjorth, Olufsen, Mehlsen, & Ottesen, ) cause to the release of products such as chemokines, cytokine, lipid mediators, nitric oxide (NO), and oxygen radicals (Arango Duque & Descoteaux, ; Markose, Kirkland, Ramachandran, & Henderson, ). On the other hand, the activation of neutrophils increases the bacteria clearance and causes inflammation and tissue damage (Park et al, ) through respiratory burst (Bae et al, ), myeloperoxidases (MPOs; Schrijver, Kemperman, Roest, Kesecioglu, & de Lange, ), proteases, and releasing several cytokine mediators (Bosmann & Ward, ; Park et al, ). Neutrophils also release neutrophil extracellular traps that lead to increase vascular inflammation and coagulation (Martinod et al, ; McDonald et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…activation of neutrophils increases the bacteria clearance and causes inflammation and tissue damage (Park et al, 2017) through respiratory burst , myeloperoxidases (MPOs; Schrijver, Kemperman, Roest, Kesecioglu, & de Lange, 2017), proteases, and releasing several cytokine mediators (Bosmann & Ward, 2013;Park et al, 2017). Neutrophils also release neutrophil extracellular traps that lead to increase vascular inflammation and coagulation (Martinod et al, 2013;McDonald et al, 2017).…”
mentioning
confidence: 99%
“…Because NDTRs and NDMVs exerted different effects on the phenotypic polarization of macrophages, we next evaluated the clinical implication of NDTRs and NDMVs in the murine models of acute and chronic inflammation. We employed an experimental sepsis model (cecalligation and puncture, CLP) to establish murine model of acute inflammation (Park et al, 2017) and a chronic dextran sulfate sodium (DSS)-induced colitis model to establish a murine model of chronic inflammation (Marcon et al, 2013). BALB/c mice were treated intraperitoneally with either NDTRs or NDMVs 30 min prior to CLP surgery and further treated on days 1, 2, and 3 after CLP surgery.…”
Section: Resultsmentioning
confidence: 99%
“…BALB/c (male, 5-8 weeks old) mice were purchased from Orient Bio. Mouse neutrophils were isolated from bone marrow of healthy mouse using neutrophil enrichment kit (Miltenyi Biotec) or EasySep™ mouse neutrophil enrichment kit (StemCell technologies) as previously described (Park et al, 2017). EVs were isolated from neutrophils stimulated with E. coli .…”
Section: Methodsmentioning
confidence: 99%